Risk Factors for Band Keratopathy in Aphakic Eyes With Silicone Oil Tamponade for Open-Globe Injuries: A Multicenter Case-Control Study - He, Kai; Liao, Mengyu; Zhu, Yun; Cui, Bohao; Chen, Haoyu; Wang, Ting; Wu, Nan; Xie, Zhenggao; Luo, Jing; Wei, Yong; Wang, Zhiliang; Zhou, Heding; et al. (Frontiers in Medicine, 2021)
Band keratopathy (BK) is a common complication in aphakic eyes with silicone oil tamponade for open-globe injury (OGI), characterized by the grayish-white opacities in the cornea, resulting in a significantly decreased vision when extending to the visual axis. To identify the risk factors for BK in aphakic eyes following vitreoretinal surgical treatment with silicone oil tamponade for OGIs, we performed a multicenter case-control study. The incidence of BK was 28% (28/100 eyes). The multivariate binary logistic regression revealed the silicone oil retention time (SORT) ≥6 months and zone III injury were significant risk factors for BK. From the hierarchical interaction, SORT ≥6 months had a significant risk for BK in eyes with rupture, aniridia, and zone III injury, while zone III injury had a significant risk for BK in eyes with rupture, incomplete/complete iris, and SORT ≥6 months. By using restricted cubic splines with three knots at the 25th, 50th, and 75th centiles to model the association of SORT with BK, we also found a marked increase in the risk for BK at ≥10 months and a slow increase after 6 months, but almost stable within 4–6 months.